Роль дипломатичних установ у започаткуванні українсько-болгарських міждержавних відносин (1918–1921 рр.) - Матяш, І. (Український історичний журнал, 2018)
Висвітлюються основні напрями діяльності болгарського дипломатичного представництва в Українській Державі та посольства Української Держави/Української Народної Республіки в Болгарському царстві. Реконструюються події,
пов’язані зі встановленням і розвитком українсько-болгарських дипломатичних відносин у 1918–1921 рр., з’ясовується роль перших представників Болгарії
в Україні та України – у Болгарії (І.Шишманова й О.Шульгина) при реалізації
міждержавних домовленостей, викладених у Брестському мирному договорі,
обстоюванні державних інтересів та захисті прав громадян своїх країн. Українсько-болгарські зносини в період між зимою 1918 та літом 1921 рр. розглядаються як вдала спроба встановлення міждержавних відносин відповідно до норм
міжнародного права. Дипломатичні представники обох країн отримали свої повноваження згідно з Брестським мирним договором. Обрання такого типу дипломатичного представництва, як посольство, також свідчило про взаємну повагу
між двома державами. Близькими були й завдання дипломатичних представництв, з очевидно більш вираженим економічним інтересом із болгарського боку
та політичним – з українського. Вітчизняне представництво докладало максимальних зусиль у справі інформування болгарського суспільства про українську національну ідею та боротьбу України за державну незалежність. Посольства обох країн припинили свою діяльність через не залежні від них обставини, однак заклали підвалини українсько-болгарських міждержавних відносин. The article describes the main approaches of activity of the Bulgarian diplomatic
representation in the Ukrainian State and the Embassy of the Ukrainian State/
Ukrainian People’s Republic in the Bulgarian Kingdom. The aim of the research was to
reconstruct the events associated with the establishment and development of Ukrainian-
Bulgarian diplomatic relations in 1918–1921, clarifying the role of the first Bulgarian
representatives in Ukraine and Ukraine in Bulgaria (I.Shishmanov and O.Shul’hyn)
in the implementation of the intergovernmental the agreements set forth in the Brest
Peace Treaty, the defense of state interests and the protection of the rights of citizens of
their countries. The track records of the Ukrainian and Foreign historiography were
taken into consideration in the article are taken into account. The source database
includes archival information, periodicals, memoirs of the direct participants of the
events. Ukrainian-Bulgarian relations between the winter of 1918 and the summer
of 1921 are considered as a successful attempt to establish interstate relations in
accordance with the norms of international law. The diplomatic representatives of both
countries received their credentials under the Brest Peace Treaty. It is indicated that
the election of such a type of diplomatic representation as the embassy also testified to
the mutual respect of the states. The tasks of the diplomatic missions were also close,
with obviously more marked economic interest from the Bulgarian side and political –
from the Ukrainian one. The Ukrainian delegation made every effort to truly inform
the Bulgarian society about the Ukrainian national idea and Ukraine’s struggle for
state independence. The embassies of both countries have ceased their activities due
to circumstances independent thereon (the Bulgarian Embassy existed for over seven
months, while the Ukrainian Embassy existed for nearly three years), but facilitated
the basis for interstate relationship between Ukraine and Bulgaria, featured by mutual
recognition and mutual respect.